AtMYB32 regulates the ABA response by targeting ABI3, ABI4 and ABI5 and the drought response by targeting CBF4 in Arabidopsis. (September 2021) - Li, Xinmei; Zhong, Ming; Qu, Lina; Yang, Jiaxin; Liu, Xueqing; Zhao, Qiang; Liu, Xuanming; Zhao, Xiaoying
Highlights: AtMYB32 is induced by ABA and repressed by drought stress. AtMYB32 promotes ABA-mediated seed germination by targeting ABI3, ABI4 and ABI5 . Mutation of AtMYB32 enhances plant drought tolerance. AtMYB32 reduces drought tolerance via ABA-independent manner by targeting CBF4 . Abstract: The Arabidopsis thaliana R2R3-MYB transcription factor AtMYB32 and its homologs AtMYB4 and AtMYB7 play crucial roles in the regulation of phenylpropanoid metabolism. In addition, AtMYB4 and AtMYB7 are involved in the response to abiotic stress. However, the function of AtMYB32 remains unclear. In this study, we found that AtMYB32 is induced by abscisic acid (ABA) and repressed by drought stress. AtMYB32 positively regulates ABA-mediated seed germination and early seedling development. The expression of ABSCISIC ACID-INSENSITIVE 3 ( ABI3 ), ABI4 and ABI5, which encode key positive regulators of ABA signaling, was upregulated in response to ABA in AtMYB32 -overexpressing plants and downregulated in the atmyb32-1 mutant. In addition, we found that the atmyb32-1 mutant was drought resistant. Consistent with the drought-resistant phenotype, the transcript levels of C-repeat binding factor 4 ( CBF4 ) were higher in the atmyb32-1 mutant in response to drought stress. Electrophoretic mobility shift assays (EMSAs) and chromatin immunoprecipitation (ChIP) assays revealed that AtMYB32 binds directly to the ABI3, ABI4, ABI5 and CBF4 promoters both in vitro and in vivo . Genetically, ABI4 was found to be epistatic to AtMYB32 for ABA-induced inhibition of seed germination and early seedling development. Taken together, our findings revealed that AtMYB32 regulates the ABA response by directly promoting ABI3, ABI4 and ABI5 expression and that the drought stress response likely occurs because of repression of CBF4 expression.